Assessment of selected heavy metal concentration in fresh and grilled beef - A case study in East Legon, Ghana - Frederick Adzitey (International Journal of One Health, 2018)
Aim: Contamination of meat by heavy metals is a concern due to their possible toxicity and effects on human health. The present study was undertaken to determine the presence and concentration of iron (Fe), zinc (Zn), copper (Cu), calcium (Ca), manganese (Mg), lead (Pb), and cadmium (Cd) in the fresh and grilled beef sold by kebab sellers in East Legon.